Using Ant Colony Optimization Clustering Algorithm with Power-Efficient Gathering in Sensor Information Systems Protocol - Jawad, Talib M; Ali, Noor A (Al-Nahrain Journal of Science, 2018)
Power-Efficient Gathering in Sensor Information Systems (PEGASIS) protocol is energy efficient protocols designed to prolong the lifetime of the network by reduction of energy consumption. In this paper a modification is proposed to the PEGASIS algorithm where sensor nodes are clustered in groups, clustering is done by Ant colony optimization algorithm, and each group is treated as PEGASIS. In addition, the proposed algorithm used rechargeable sensor nodes. Two parameters are searched to select chain leader: Euclidean distance of sensor node to the base station and residual energy of sensor node. Each cluster head data is transmitted directly to the base station. Simulation results showed the proposed algorithms improved in comparison with original PEGASIS. PEGASIS